Ultrasonic navigation – a single way for identification of brachial plexus nerves in patient with severe vascular pathology (Pain medicine, 2018)
The article discusses the successful experience of using ultrasound imaging of the brachial plexus nerves to perform a supraclavicular block of the brachial plexus with an additional block of n. cutaneus brachii medialis and n. intercostobrachialis in a patient with severe vascular pathology with lack of sensitivity and movements in the hand. The authors describe this technique in detail.
Keywords: ultrasound navigation; block of the brachial plexus; ultrasound in anesthesiology